Ga-doped ZnO nanoparticles synthesized by sonochemical-assisted process. (2018) - Santibenchakul, S.; Sirijaturaporn, P.; Mekprasart, W.; Pechrapa, W.
Abstract: In this work, the experimental work has been conducted on the synthesis of Gallium (Ga)- doped zinc oxide (ZnO) nanoparticles with different doping concentration (0-5% at.) via sonochemical process. The precursors of Ga-doped ZnO nanoparticle were sourced by zinc acetate dehydrate and gallium (III) nitrate hydrate, respectively. Ammonia (NH3 ) was chosen as a precipitating agent in sonochemical process. The sonochemical time was operated for 10 min by a direct-immersion ultrasonic horn using Sonic model VCX 750 (750W, 20 KHz). Structural properties and morphologies were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results indicated that Ga doped ZnO powder after the synthesis were obtained in ultrafine structure that different form with pure ZnO. XRD analysis revealed that the pattern of Ga doped ZnO powder showed good crystallinity with the wurtzite structure due to the preferred orientation direction and crystallization. Ga doping concentration plays a key role in significant change of ZnO structures.